2023
DOI: 10.1126/sciadv.adh5517
|View full text |Cite
|
Sign up to set email alerts
|

Earliest curry in Southeast Asia and the global spice trade 2000 years ago

Abstract: The global spice trade has played an essential role in world history. However, because of poor preservation conditions, archaeobotanical remains of spices have been limited in archaeological contexts until now. This study reports evidence for spice processing from the archaeological site of Oc Eo in southern Vietnam, an entrepôt of the state of Funan that was occupied during the early centuries CE. Analysis of plant microremains recovered from the surfaces of Oc Eo grinding stone tools thought to be of South A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Ginger has been used as medicine and a spice in India and China since ancient times [ 116 ]. In India, ginger starch has been identified at the site of Farmana [ 117 ], and in China, ginger starch granules have been identified at the Neolithic Dadiwan site [ 118 ], and Liu et al [ 119 ] found starch remains associated with the production of alcoholic beverages in containers dating to 9000–7000 cal BP. Recently, ginger starch grains have been identified on grinding stones from Vietnam [ 117 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginger has been used as medicine and a spice in India and China since ancient times [ 116 ]. In India, ginger starch has been identified at the site of Farmana [ 117 ], and in China, ginger starch granules have been identified at the Neolithic Dadiwan site [ 118 ], and Liu et al [ 119 ] found starch remains associated with the production of alcoholic beverages in containers dating to 9000–7000 cal BP. Recently, ginger starch grains have been identified on grinding stones from Vietnam [ 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…In India, ginger starch has been identified at the site of Farmana [ 117 ], and in China, ginger starch granules have been identified at the Neolithic Dadiwan site [ 118 ], and Liu et al [ 119 ] found starch remains associated with the production of alcoholic beverages in containers dating to 9000–7000 cal BP. Recently, ginger starch grains have been identified on grinding stones from Vietnam [ 117 ]. Ginger was one of the first Oriental spices to reach the Greeks and Romans about 2000 years ago, was known in France and Germany since the ninth century, England since the tenth century [ 115 , 116 ] and reached Scandinavia only in the 15 th century [ 120 ].…”
Section: Discussionmentioning
confidence: 99%